2009
DOI: 10.5194/bg-6-1043-2009
|View full text |Cite
|
Sign up to set email alerts
|

The ACCENT-VOCBAS field campaign on biosphere-atmosphere interactions in a Mediterranean ecosystem of Castelporziano (Rome): site characteristics, climatic and meteorological conditions, and eco-physiology of vegetation

Abstract: Abstract. Biosphere-atmosphere interactions were investigated on a sandy dune Mediterranean ecosystem in a field campaign held in 2007 within the frame of the European Projects ACCENT and VOCBAS. The campaign was carried out in the Presidential estate of Castelporziano, a periurban park close to Rome. Former campaigns (e.g. BEMA) performed in Castelporziano investigated the emission of biogenic volatile organic compounds (BVOC). These campaigns focused on pseudosteppe and evergreen oak groves whereas the contr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 72 publications
4
28
0
Order By: Relevance
“…29 Most trees and shrubs of the mixed Mediterranean forest were shown to be minor isoprene emitters from gas exchange studies at the leaf level. 2,3 Our measurements confirmed that monoterpenes dominated biogenic emissions (total BEF of 1747 μg m −2 h −1 ), while isoprene emission were 1 order of magnitude lower (Figure 1). PTR-TOF-MS operating in H 3 O + mode detects isoprene at the same m/z as the fragment of methyl-butenol (m/z 69.070), 39 a compound emitted from pines in western North America, 40 whereas methyl-butenol was not found in Mediterranean stone pines.…”
Section: ■ Materials and Methodssupporting
confidence: 69%
See 4 more Smart Citations
“…29 Most trees and shrubs of the mixed Mediterranean forest were shown to be minor isoprene emitters from gas exchange studies at the leaf level. 2,3 Our measurements confirmed that monoterpenes dominated biogenic emissions (total BEF of 1747 μg m −2 h −1 ), while isoprene emission were 1 order of magnitude lower (Figure 1). PTR-TOF-MS operating in H 3 O + mode detects isoprene at the same m/z as the fragment of methyl-butenol (m/z 69.070), 39 a compound emitted from pines in western North America, 40 whereas methyl-butenol was not found in Mediterranean stone pines.…”
Section: ■ Materials and Methodssupporting
confidence: 69%
“…Site details and BEF calculation methods concerning previous campaigns have been described previously. 2,4,13 Our recent field campaign was carried out in the mixed oak and pine forest between September and October 2011. The experimental site (41.744N, 12.411E) named "Castello" is primarily dominated by Pinus pinea (stone pine), Quercus ilex (holm oak), and Quercus suber (cork oak).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations